Evaluation of an Immersed Boundary Method for solving the fluid structure interaction problem in refrigeration compressor valves - Gasche, José L. [UNESP]; Barbi, Franco (My University, 2014)
In refrigeration compressors, the suction and discharge valves are responsible for the retention of the refrigerant from the suction chamber to the cylinder and passage from the cylinder to the discharge chamber. As the opening and closing of the valves are caused by the forces produced by the refrigerant flow, the understanding of the flow through the valve is of fundamental importance in order to enhance the efficiency of the valve system. The numerical simulation of the flow is an efficient method to perform this task. Due to the complex geometry usually found in this type of valve, simplified geometries have been used to represent the valve, particularly the radial diffuser. This work presents a numerical simulation of the unsteady flow through a more realistic geometric model for the suction valve including the movement of the reed. An Immersed Boundary Method (IBM) with the Multi-Direct Forcing Scheme is used to represent the valve geometry and to solve the 3D unsteady flow for an imposed angular movement to the reed. An adaptive mesh dynamically refined is used for representing the flow domain. The governing equations are solved by a projection method, using a semi-implicit second-order scheme for time integration. The systems of algebraic equations are solved by a Multigrid-Multilevel technique. Results for pressure and velocity fields and for pressure profiles on the reed surface were obtained for Reynolds number varying from 1, 000 to 8, 000. The results show that the IBM is a very good alternative for solving the flow through reed type valves with complex geometry.
Keywords: Compressor; Fluid-structure interaction; Immersed boundary method; Valve